Description of the second- and third-instar larvae of Hydrovatus crassulus Sharp, 1882 (Coleoptera: Dytiscidae: Hydrovatini) - Michat, Mariano C. (Zootaxa, 2021)
The second- and third-instar larvae of the diving-beetle species Hydrovatus crassulus Sharp, 1882 are described and illustrated, including detailed morphometric and chaetotaxic analyses of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of this species lack the parietal pore PAo, the premental seta LA3 and the urogomphal seta UR8, and have the sensillum MN2 shaped as a short hair-like seta and the ventral surface of the abdominal segments II–V sclerotized. All these characteristics are shared with the other species of Hydrovatus Motschulsky, 1853 known in detail (H. caraibus Sharp, 1882) and therefore are considered diagnostic for the genus. Hydrovatus crassulus also characterizes by the presence of a small galea, which reinforces the hypothesis that this structure is part of the ancestral condition of Hydrovatus. Larvae of H. crassulus differ from those of H. caraibus in having a smaller size, a smaller ratio U/LAS, and a larger ratio U1/U2, and also in the presence (in most cases) of a secondary seta on the anteroventral surface of femur.